Bone and cartilage metaplasia in calcific aortic stenosis - Zorić, Jelena; Vuković, Miloš; Lovrenski, Aleksandra; Samardžija, Golub; Andrejić Višnjić, Bojana; Panjković, Milana (Vojnosanitetski pregled, 2021)
Background/Aim. Calcification is a frequent change in aortic cusps and the most frequent cause for the occurrence of aortic valve stenosis. Recent studies have shown that the process of aortic calcification is often active and closely related to the formation of bone tissue in calcific aortic stenosis. The aim was to analyze the demographic characteristics of patients with calcific aortic stenosis, the most common symptoms, comorbidities and risk factors, incidence of bone and cartilage metaplasia and its possible association with the present comorbidities, as well as its clinical importance. Methods. We retrospectively analyzed the medical records of 115 patients referred to the University Hospital from January 2013 to December 2015. Results. Calcific aortic stenosis occurred more frequently in males. The average age of patients was 67.3 years. The majority of patients were non-smokers, overweight. The most common clinical symptoms were fatigue, shortness of breath and chest pain. Eighteen (15.6%) patients had no symptoms. Seventeen (14.8%) patients had cartilaginous and osseous metaplasia. Gender, age, smoking and body mass index (BMI) had the same distribution among patients with and without metaplasia. Metaplasia was equally prevalent among patients with moderate, severe and critical aortic stenosis. Conclusion. Age, sex, smoking, BMI and blood pressure values are not risk factors neither for osseous nor for cartilaginous metaplasia.